Penerapan Bauran Pemasaran Efektif dalam Meningkatkan Daya Tarik Lembaga Pendidikan Islam di Ponorogo - Faradilla Detisha; Alin Muzakky; Nur Syaidah Khasanah; Rossa Nurmala Dewi; Dian Pratiwi (Excelencia: Journal of Islamic Education & Management, 2023)
Abstract This article aims to analyze the implementation of an effective marketing mix in enhancing the attractiveness of MA Darul Huda, an Islamic boarding school located in Indonesia. Islamic boarding schools play a crucial role in providing quality Islamic education and shaping students' characters. However, the increasingly competitive education industry demands effective marketing strategies to attract prospective students and parents. This study adopts a case study approach and qualitative research methods. Data were collected through observations and interviews with teachers, staff, and students at MA Darul Huda. The findings indicate that the implementation of effective marketing strategies can significantly enhance the appeal of Islamic boarding schools. The successful marketing strategies implemented at MA Darul Huda include appropriate market segmentation, the development of innovative educational programs, promotion through social media and websites, and establishing good relationships with parents. The combination of these strategies has successfully improved the image and reputation of the Islamic boarding school within the education community. The results of this research have practical implications for the management of Islamic boarding schools in designing and implementing effective marketing strategies to enhance the attractiveness and sustainability of educational institutions. Additionally, this article contributes theoretically by highlighting the application of marketing mix in the context of Islamic education. Keywords: marketing mix, Islamic boarding school, attractiveness, marketing strategy, Islamic education. Abstrak Artikel ini bertujuan untuk menganalisis penerapan bauran pemasaran yang efektif dalam meningkatkan daya tarik MA Darul Huda, sebuah madrasah aliyah yang terintegrasi dengan Pondok Pesantren Darul Huda Mayak Ponorogo. Madrasah aliyah memainkan peran penting dalam menyediakan pendidikan Islam yang berkualitas dan membentuk karakter siswa. Namun, semakin kompetitifnya industri pendidikan menuntut adanya strategi pemasaran yang efektif untuk menarik minat calon siswa dan orang tua. Penelitian ini menggunakan pendekatan studi kasus dan metode penelitian kualitatif. Data diperoleh melalui observasi dan wawancara terhadap guru, staf, dan siswa di MA Darul Huda. Hasil penelitian menunjukkan bahwa penerapan strategi pemasaran yang efektif dapat secara signifikan meningkatkan daya tarik madrasah aliyah. Strategi pemasaran yang berhasil diterapkan di MA Darul Huda meliputi segmentasi pasar yang tepat, pengembangan program pendidikan yang inovatif, promosi melalui media sosial dan website, serta menjalin hubungan yang baik dengan orang tua siswa. Kombinasi strategi ini berhasil meningkatkan citra dan reputasi madrasah aliyah dalam komunitas pendidikan. Hasil penelitian ini memberikan implikasi praktis bagi pengelola madrasah aliyah dalam merancang dan menerapkan strategi pemasaran yang efektif untuk meningkatkan daya tarik dan keberlanjutan lembaga pendidikan. Selain itu, artikel ini juga memberikan kontribusi teoretis dengan menyoroti penerapan bauran pemasaran dalam konteks pendidikan Islam. Kata Kunci: bauran pemasaran, madrasah aliyah, daya tarik, strategi pemasaran, pendidikan Islam.